Pengaruh Metode Tahsin Al-Qur’an Terhadap Penguasaan Makharijul Huruf Peserta Didik Di Ban Samoh School Provinsi Narathiwat, Thailand - Angraini, Herlindyah; Wahyuni, Sri; Siregar, Rosmaimuna (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This research was motivated by the lack of students' ability to read the Al-Qur'an properly and correctly, especially in pronouncing the makharijul letters. This research aims to find out how the use of the Al-Qur'an tahsin method affects mastery of makharijul letters. The population of this research is students at Ban Samoh Scool, Narathiwat Province, Thailand, academic year 2023, totaling 34 students. Using quantitative research with experimental methods. The results of this research show that in the pre-test percentage, 13 students got very low scores (38.2%), 11 students got low scores (32.4%), 10 students got medium scores (29.4%). %). So looking at the existing percentages it can be said that students' understanding of makharijul letters is still relatively low. After applying the tahsin method and obtaining the results of applying the Al-Qur'an tahsin method, as many as 5 students got low grades (14.7%), as many as 19 students got medium grades (55.9%), as many as 3 students got grades high (8.9%) and as many as 7 students got very high scores (20.5%). From the results of the post test, it can be seen that there is an increase in students' understanding of makharijul letters